The Influence of Entrepreneurship Education and Technopreneurship Literacy on Entrepreneurial Intention with Self-Efficacy as an Intervening Variable in Generation Z - Isma, Andika; Nur Halim; Andi Anggi Kemalasari; Muhammad Rakib; Hajar Dewantara (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aims to identify whether entrepreneurship education and technopreneurship literacy among students contribute to interest in entrepreneurship through self-efficacy among Generation Z in Makassar City. This research is included in the quantitative research category with a population of 500 Generation Z from Vocational High Schools in Makassar City and a sample of 100 people. Data was collected using questionnaire and documentation techniques. The analysis technique used is path analysis using SPSS software. The research results show that entrepreneurship education and technopreneurship literacy, both directly and indirectly, contribute positively and significantly to interest in entrepreneurship through self-efficacy among Generation Z in Makassar City. Based on the results of this research, entrepreneurship education and technopreneurship literacy are very important to be taught and given to Generation Z, especially in the school environment. This education should not only be taught in one particular department but should be taught in all departments. This is because entrepreneurship education and technopreneurship literacy can increase students' self-efficacy, which in turn can contribute to increasing interest in entrepreneurship among students.